Improving the quantity, quality and transparency of data used to derive radionuclide transfer parameters for animal products. 1. Goat milk. (April 2016) - Howard, B.J.; Wells, C.; Barnett, C.L.
Abstract: Under the MODARIA (Modelling and Data for Radiological Impact Assessments Programme of the International Atomic Energy Agency), there has been an initiative to improve the derivation, provenance and transparency of transfer parameter values for radionuclides. The approach taken for animal products is outlined here and the first revised table for goat milk is provided. Data from some references used in TRS 472 were removed and reasons given for removal. Particular efforts were made to improve the number of CR (concentration ratio) values which have some advantages over transfer coefficients. There is little difference in most of the new CR and Fm (transfer coefficient) values for goat milk compared with those in TRS 472. In TRS 472, 21 CR values were reported for goat milk. In the 2015 dataset for goat milk CR values for a further 14 elements are now included. The CR and Fm values for only one element (Co) were removed. Highlights: The derivation, transparency and provenance of animal product transfer values has been improved. The first revision of one of these tables is reported for goat milk. The number of reported Concentration ratio (CR) values has considerably increased.